Реализация модели учебного курса на основе технологий сети интернет - Шубин, И. Ю.; Алисейко, З. А.; Выродов, А. П.; Дударь, В. В. (УАДО, 2002)
The paper deals with development of software implementation of a subject matter model that forms pan of the mathematical model complex of computer-based training systems. The approach, offered in the work, is based on the hypertext technology and allows with the least costs to adapt a training system for operation in Internet, and also to increase integration between separate components of the system.
Keywords: модель учебного курса; дистанционное обучение